Integration of GPS and VLC for outdoor and indoor target detection - Chen, Liangquan (2014)
With the rising trend of low energy IC components, LED (Light Emitting Diode) will soon take the dominance in indoor lighting. GPS (Global Positioning System) has its limitation on reaching indoor environment. Solutions to provide indoor position system had been the interest of researchers and engineers. This project was intended to provided an indoor positioning solution using VLC (Visible Light Communication) so that people can pinpoint any target globally, either indoor or outdoor. Indoor using VLC technology, outdoor uses GPS technology.